Pattern of antibiotic prescription and resistance profile of common bacterial isolates in the internal medicine wards of a tertiary referral centre in Nigeria. Issue 2 (June 2015) - Iliyasu, Garba; Dayyab, Farouq M.; Bolaji, Tiamiyu A.; Habib, Zaiyad G.; Takwashe, Isa M.; Habib, Abdulrazaq G.
Highlights: Inappropriate antibiotic prescription is common in Nigeria. There was frequent use of third-generation cephalosporins as empirical therapy, with de-escalation in only a handful of cases. Antibiotic resistance among common bacterial isolates is common. This highlights the need for introduction of antibiotic guidelines. Abstract: Indiscriminate and excessive use of antibiotics is the major driver to the development of bacterial resistance, which is now a global challenge. Information regarding antibiotic use in Nigerian hospitals is lacking. This study examined the pattern of antibiotic prescription in a tertiary hospital in Nigeria. In a retrospective survey, case records of patients who were admitted into the medical wards over a 6-month period were reviewed. A pre-formed questionnaire was administered that sought information such as sociodemographic data, drug data, basis of prescription and other relevant information on all patients who received antibiotics. Data were analysed using SPSS for Windows v.16. Of 412 patients admitted into the internal medicine ward during the study period, 202 (49.0%) received antibiotics, of whom 125 (61.9%) received more than one antibiotic. Overall there were 334 antibiotic prescriptions. Community-acquired pneumonia (67/202; 33.2%) was the leading cause of antibiotic prescription, and ceftriaxone (132/334; 39.5%) was the most commonly prescribed antibiotic. The parenteral route was the commonest route of administration (270/334; 80.8%) and most of the prescriptions were empirical (323/334; 96.7%). Antimicrobial resistance among common bacterial isolates was noted. Inappropriate antibiotic prescription is common. There was frequent use of third-generation cephalosporins as empirical therapy, with de-escalation in only a handful of cases. This highlights the need for introduction of antibiotic guidelines.